Preparation method of double-shell abrasive material coated with SiO2 / CeO2 by taking nano PMMA (polymethyl methacrylate) as inner core

By covering SiO2 and CeO2 shells on PMMA microspheres, nano-PMMA/SiO2/CeO2 composite abrasives are prepared, which solves the problems of poor dispersion and high surface roughness in the polishing process of traditional abrasives, and achieves the effects of efficient polishing and low surface roughness.

CN119592304AActive Publication Date: 2025-03-11INNER MONGOLIA UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411768261.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

Traditional single inorganic polishing abrasives are difficult to achieve satisfactory polishing effects during chemical mechanical polishing, and the dispersion of cerium-based rare earth polishing powder is poor, which easily leads to agglomeration and affects the polishing quality.

Method used

NanoPMMA is used as the core and SiO2 shells are coated on the outside of the PMMA microspheres in turn to prepare a bicanthous abrasive. The method includes preparing PMMA microspheres for soap-free emulsion polymerization, preparing PMMA/SiO2 composite microspheres for sol-gel method, and adding CeO2 layers through uniform precipitation method to form nano PMMA/SiO2/CeO2 composite abrasives.

Benefits of technology

On the basis of ensuring polishing efficiency, the abrasive further reduces the surface roughness, meets the polishing quality requirements of high-end precision components, and has good flexibility, chemical stability and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592304A_ABST
    Figure CN119592304A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a SiO2 / CeO2 double-shell abrasive with nano PMMA as an inner core, and relates to the technical field of composite abrasives. The method comprises the following steps: firstly, by adopting a boiling system soap-free emulsion polymerization method, taking methyl methacrylate as a monomer, adding a coupling agent 3-(methacryloyloxy) propyltrimethoxysilane, and initiating a polymerization reaction by using 2, 2 '-azobis (isobutylamidine) dihydrochloride, so as to prepare PMMA (Polymethyl Methacrylate) microspheres with controllable particle size and better monodispersity; then preparing strawberry type PMMA / SiO2 composite microspheres by taking tetraethyl silicate as a raw material and adopting a sol-gel method; and finally, by taking soluble cerium salt as a raw material and hexamethylenetetramine as a precipitator, preparing the double-shell PMMA / SiO2 / CeO2 composite abrasive material uniformly coated with the nano CeO2 particles by adopting a homogeneous precipitation method. The grinding material is provided with a flexible inner core and more surface active sites, and lower surface roughness and higher material removal rate can be obtained in ultra-precision surface polishing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite abrasives, and in particular to a method for preparing a double-shell abrasive with nano PMMA as a core and coated with SiO2 / CeO2. Background Art

[0002] In today's industrial manufacturing field, the surface quality requirements for high-end precision components such as optical components are becoming more and more stringent. Take polishing KDP crystals as an example. As large-sized optical components, KDP crystals are brittle and have low hardness, and the surface roughness must reach the sub-nanometer level. Chemical mechanical polishing (CMP) is a unique technology used in surface processing. It achieves material surface flatness through the synergistic effect of chemical corrosion and mechanical friction. It is currently one of the mainstream technologies for obtaining ultra-smooth surfaces.

[0003] In the process of chemical mechanical polishing, the selection of abrasive types plays a vital role. Traditional single inorganic polishing abrasives are often difficult to achieve satisfactory results in the actual polishing process. Cerium-based rare earth polishing powder has the advantages of high polishing efficiency, easy cleaning after polishing, and relatively little pollution to the environment. However, it has poor dispersibility and is prone to agglomeration, which will have an adverse effect on the polishing quality. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a double-shell abrasive with nano PMMA as a core coated with SiO2 / CeO2; the method uses nano PMMA as a core, and sequentially coats SiO2 and CeO2 shells on the outside of PMMA microspheres to prepare a double-shell abrasive; the abrasive further reduces the surface roughness on the basis of fully ensuring the polishing efficiency, thereby meeting the demand for polishing quality of high-end precision components.

[0005] The technical solution adopted by the present invention is as follows:

[0006] The present invention provides a method for preparing a double-shell abrasive with a nano PMMA core coated with SiO2 / CeO2; the method comprises the following steps:

[0007] Step 1, preparing PMMA microspheres by soap-free emulsion polymerization: washing methyl methacrylate with sodium hydroxide solution, adding the washed methyl methacrylate into deionized water, and then adding 3-(methacryloyloxy)propyltrimethoxysilane to prepare a mixed solution A, ultrasonically dispersing the mixed solution A, and heating it to boiling in a constant temperature oil bath; adding 2,2'-azobisisobutylamidine dihydrochloride aqueous solution under stirring conditions to react, and cooling after the reaction is completed to obtain a uniformly dispersed PMMA microsphere emulsion.

[0008] Step 2, preparing PMMA / SiO2 nanocomposite microspheres by sol-gel method: taking the PMMA microsphere emulsion prepared in step 1, adding it into anhydrous ethanol for ultrasonic dispersion, adding ammonia water to adjust the pH value to 8-10 to obtain solution B; preparing tetraethyl silicate anhydrous ethanol solution C with a concentration of 40-200 g / L, and then dropping solution C into the continuously stirred solution B, and heating the reaction in a constant temperature water bath; centrifuging the final product, and repeatedly washing it with deionized water and anhydrous ethanol, and then drying it, and grinding it to obtain core-shell structured silica-coated polymethyl methacrylate nanocomposite microspheres.

[0009] Step 3, prepare PMMA / SiO2 / CeO2 composite abrasive by uniform precipitation method: take the silica-coated polymethyl methacrylate nanocomposite microspheres prepared in step 2, add them into deionized water for ultrasonic dispersion to obtain solution D; add soluble cerium salt to solution D, and then add hexamethylenetetramine to obtain solution E, heat it in a constant temperature water bath, and react under continuous stirring; the final product is centrifuged and repeatedly washed with deionized water and anhydrous ethanol, and then dried, and ground to obtain PMMA / SiO2 / CeO2 nanocomposite abrasive with a double shell structure.

[0010] Furthermore, in step 1, the concentration of the sodium hydroxide solution is 10%.

[0011] Furthermore, in step 1, the dosage of methyl methacrylate and deionized water is 10-30 g: 100-150 ml; the dosage of 3-(methacryloyloxy)propyltrimethoxysilane and methyl methacrylate is 1-4 g: 10-30 g; 20 ml of 50-200 g / L 2,2'-azobisisobutylamidine dihydrochloride aqueous solution is added, react for 1.5-3 hours, and then cool to obtain a uniformly dispersed PMMA microsphere emulsion.

[0012] Furthermore, in step 2, 10 to 60 ml of the PMMA microsphere emulsion prepared in step 1 is added to 50 to 100 ml of anhydrous ethanol for ultrasonic dispersion; 25 ml of solution C is added dropwise to the continuously stirred solution B; the constant temperature water bath is heated to 30 to 60° C., and the reaction time is 4 to 7 hours.

[0013] Further, in step 3, 0.5-4 g of PMMA / SiO2 composite microspheres are added to 100-250 ml of deionized water for ultrasonic dispersion to obtain solution D; 1-5 g of soluble cerium salt is added to solution D, and then 2-10 g of hexamethylenetetramine is added to obtain solution E; a constant temperature water bath is used for heating at a temperature of 60-85°C, and the reaction is carried out for 2-4 hours under continuous stirring.

[0014] Furthermore, in step 3, the soluble cerium salt is any one of cerium nitrate, cerium sulfate and cerium chloride, or a combination thereof.

[0015] The beneficial effects of the present invention are as follows: the present invention discloses a preparation method of a double-shell abrasive with nano PMMA as a core coated with SiO2 / CeO2, the method comprising the following steps: firstly, a boiling system soap-free emulsion polymerization method is adopted, methyl methacrylate is used as a monomer, and a coupling agent 3-(methacryloyloxy)propyltrimethoxysilane is added, and a polymerization reaction is initiated by 2,2'-azobisisobutylamidine dihydrochloride to prepare PMMA microspheres with controllable particle size and good monodispersity; then, tetraethyl silicate is used as a raw material, and a sol-gel method is adopted to prepare strawberry-shaped PMMA / SiO2 composite microspheres; finally, a soluble cerium salt is used as a raw material, hexamethylenetetramine is used as a precipitant, and a uniform precipitation method is adopted to prepare a double-shell PMMA / SiO2 / CeO2 composite abrasive with nano CeO2 particles uniformly coated.

[0016] The PMMA / SiO2 / CeO2 composite abrasive prepared by the present invention has good flexibility, chemical stability and wear resistance. The PMMA core has plasticity, and SiO2 and CeO2 are respectively covered on it as shell layers, and this core-shell structure can effectively buffer external friction. The silicon atoms of the SiO2 layer and the oxygen atoms of the CeO2 layer form a stable interface structure through covalent bonds. During the polishing process, the CeO2 layer can form a lubricating film on the surface of the polished crystal, so that mechanical interaction and intermolecular interaction occur simultaneously between the CeO2 layer and the surface of the polished crystal, reducing the direct friction between the PMMA / SiO2 / CeO2 composite abrasive and the surface of the polished crystal, thereby reducing the surface roughness of the crystal. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM image of PMMA microspheres prepared in Example 1 of the present invention.

[0019] Figure 2 The infrared spectra of PMMA microspheres, PMMA / SiO2 composite microspheres, and PMMA / SiO2 / CeO2 composite abrasives prepared in Example 1 of the present invention are shown.

[0020] Figure 3 This is the XRD diagram of the PMMA / SiO2 composite microspheres and PMMA / SiO2 / CeO2 composite abrasives prepared in Example 1 of the present invention.

[0021] Figure 4 It is a TEM image of PMMA / SiO2 composite microspheres prepared without adding MPS and with adding 2g MPS in the present invention.

[0022] Figure 5 It is the SEM picture of PMMA / SiO2 composite microspheres prepared at three dosages of tetraethyl silicate TEOS of the present invention.

[0023] Figure 6 TEM images of PMMA / SiO2 / CeO2 composite abrasives prepared with different amounts of cerium nitrate in the present invention.

[0024] Figure 7 1 is an AFM image of the PMMA / SiO2 / CeO2 composite abrasive prepared in Example 1 of the present invention and the PMMA / CeO2 composite abrasive prepared in Comparative Experiment 1 after polishing the KDP crystal. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is described in detail below by specific examples, but the content of the present invention is not limited to the following examples. The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0027] Example 1

[0028] A method for preparing a double-shell abrasive with a nano PMMA core coated with SiO2 / CeO2 comprises the following steps:

[0029] (1) Preparation of polymethyl methacrylate microspheres:

[0030] 20 g of methyl methacrylate was measured and washed with 10% sodium hydroxide. The washed methyl methacrylate was added to 120 ml of deionized water, and then 2 g of 3-(methacryloyloxy)propyltrimethoxysilane was added to prepare a mixed solution A. The mixed solution A was ultrasonically dispersed and heated to boiling in a constant temperature oil bath. After 5 minutes, 20 ml of a 100 g / L aqueous solution of 2,2'-azobisisobutylamidine dihydrochloride was added under stirring. After reacting for 2 hours, the mixture was cooled to obtain a uniformly dispersed PMMA microsphere emulsion.

[0031] (2) Preparation of PMMA / SiO2 composite microspheres:

[0032] Take 30 ml of the PMMA microsphere emulsion prepared in step 1 and add it to 80 ml of anhydrous ethanol for ultrasonic dispersion, and add ammonia water to adjust the pH value to 9 to obtain solution B. Prepare a 120 g / L tetraethyl silicate anhydrous ethanol solution C, and then drop 25 ml of solution C into the continuously stirred solution B, and heat it in a constant temperature water bath at 35 ° C for 5 hours. The final product is separated by a centrifuge, repeatedly washed with deionized water and anhydrous ethanol, dried in a drying oven, and ground to obtain core-shell structured silica-coated polymethyl methacrylate nanocomposite microspheres.

[0033] (3) Preparation of PMMA / SiO2 / CeO2 composite abrasive:

[0034] Take 2g of PMMA / SiO2 composite microspheres and add them to 200ml of deionized water for ultrasonic dispersion to obtain solution D; add 3g of soluble cerium salt to solution D, and then add 6g of hexamethylenetetramine to obtain solution E, which is heated in a constant temperature water bath at 75°C and reacted for 3h under continuous stirring. The final product is separated by a centrifuge, repeatedly washed with deionized water and anhydrous ethanol, dried in a drying oven, and ground to obtain a PMMA / SiO2 / CeO2 nanocomposite abrasive with a double-shell structure.

[0035] like Figure 1 The SEM image of the PMMA microspheres prepared in Example 1 of the present invention is shown. As can be seen from the figure, the PMMA microspheres prepared in the embodiment of the present invention present a good spherical shape, without agglomeration and adhesion, and the monodispersity of the PMMA microspheres is good. The average particle size of the PMMA microspheres is about 295 nm.

[0036] like Figure 2 The infrared spectra of PMMA microspheres, PMMA / SiO2 composite microspheres, and PMMA / SiO2 / CeO2 composite abrasives prepared in Example 1 of the present invention are shown. As can be seen from the figure, the FTIR curve of PMMA microspheres prepared in Example 1 of the present invention is 1730.84 cm -1 The strong absorption peak at 2994.9 cm-1 belongs to the stretching vibration peak of C=O. -1 and 2951cm -1 The characteristic peaks at 1246.7cm-1 and 1150.4cm-1 are the stretching vibration peaks of -CH3 and -CH2-, respectively, and the characteristic peaks at 1637.4cm-1 and 1150.4cm-1 are the stretching vibration peaks of COC. In addition, the stretching vibration peak of C=C in MPS also appears at 1637.4cm-1. For the FTIR curve of PMMA / SiO2 composite microspheres, the peak intensity near 1149.52cm-1 increases, which is caused by the characteristic peak of Si-O-Si stretching vibration; the symmetric and asymmetric stretching vibration peaks of Si-O bonds appear at 808.5cm-1 and 1093.9cm-1, respectively, which indicates that a SiO2 layer has grown on the surface of the PMMA microspheres. The PMMA / SiO2 / CeO2 composite abrasive has a peak intensity of 1026.4cm-1. -1 The characteristic peak at 699.3cm is the characteristic peak of Ce-O. -1 The characteristic peak at is the asymmetric stretching vibration peak of Ce-O-Ce metal oxide in the lattice, which further indicates that CeO2 grains are deposited on the surface of the abrasive.

[0037] Figure 3The XRD diagrams of the PMMA / SiO2 composite microspheres and the PMMA / SiO2 / CeO2 composite abrasives prepared in Example 1 of the present invention are shown. As can be seen from the figure, the PMMA / SiO2 composite microspheres prepared in Example 1 of the present invention have a wide diffuse peak at 2θ=13°, which is the strong peak of the amorphous diffraction of PMMA. A very wide "steamed bun peak" can be seen near 2θ=27°, which is caused by the overlap of the weak amorphous peak of PMMA and the amorphous diffraction peak of SiO2. The PMMA / SiO2 / CeO2 composite abrasive has diffraction peaks at 2θ=28.5°, 33.1°, 47.4° and 56.3°, 59.0°, 69.4°, and their positions and relative intensities are consistent with the CeO2 standard card (JCPDS 34-0394); a weak SiO2 amorphous diffraction peak appears near 2θ=21°, indicating that the CeO2 grain layer has completely covered the SiO2 particle layer, forming a PMMA / SiO2 / CeO2 double-layer core-shell structure.

[0038] Example 2

[0039] A method for preparing a double-shell abrasive with a nano PMMA core coated with SiO2 / CeO2 comprises the following steps:

[0040] (1) Preparation of polymethyl methacrylate microspheres:

[0041] 10 g of methyl methacrylate was measured and washed with 10% sodium hydroxide. The washed methyl methacrylate was added to 100 ml of deionized water, and then 1 g of 3-(methacryloyloxy)propyltrimethoxysilane was added to prepare a mixed solution A. The mixed solution A was ultrasonically dispersed and heated to boiling in a constant temperature oil bath. After 5 minutes, 20 ml of a 50 g / L aqueous solution of 2,2'-azobisisobutylamidine dihydrochloride was added under stirring. After reacting for 1.5 hours, the mixture was cooled to obtain a uniformly dispersed PMMA microsphere emulsion.

[0042] (2) Preparation of PMMA / SiO2 composite microspheres:

[0043] Take 10 ml of the PMMA microsphere emulsion prepared in step 1 and add it to 50 ml of anhydrous ethanol for ultrasonic dispersion, and add ammonia water to adjust the pH value to 8 to obtain solution B. Prepare a 40 g / L tetraethyl silicate anhydrous ethanol solution C, and then drop 25 ml of solution C into the continuously stirred solution B, and heat it in a constant temperature water bath at 30 ° C for 4 hours. The final product is separated by a centrifuge, repeatedly washed with deionized water and anhydrous ethanol, dried in a drying oven, and ground to obtain core-shell structured silica-coated polymethyl methacrylate nanocomposite microspheres.

[0044] (3) Preparation of PMMA / SiO2 / CeO2 composite abrasive:

[0045] 0.5g of PMMA / SiO2 composite microspheres were added to 100ml of deionized water for ultrasonic dispersion to obtain solution D; 1g of soluble cerium salt was added to solution D, and then 2g of hexamethylenetetramine was added to obtain solution E, which was heated in a constant temperature water bath at 60°C and reacted for 2h under continuous stirring. The final product was separated by a centrifuge, repeatedly washed with deionized water and anhydrous ethanol, dried in a drying oven, and ground to obtain a PMMA / SiO2 / CeO2 nanocomposite abrasive with a double-shell structure.

[0046] Example 3

[0047] A method for preparing a double-shell abrasive with a nano PMMA core coated with SiO2 / CeO2 comprises the following steps:

[0048] (1) Preparation of polymethyl methacrylate microspheres:

[0049] 30 g of methyl methacrylate was measured and washed with 10% sodium hydroxide. The washed methyl methacrylate was added to 150 ml of deionized water, and then 4 g of 3-(methacryloyloxy)propyltrimethoxysilane was added to prepare a mixed solution A. The mixed solution A was ultrasonically dispersed and heated to boiling in a constant temperature oil bath. After 5 minutes, 20 ml of a 200 g / L aqueous solution of 2,2'-azobisisobutylamidine dihydrochloride was added under stirring. After reacting for 3 hours, the mixture was cooled to obtain a uniformly dispersed PMMA microsphere emulsion.

[0050] (2) Preparation of PMMA / SiO2 composite microspheres:

[0051] Take 60 ml of the PMMA microsphere emulsion prepared in step 1 and add it to 100 ml of anhydrous ethanol for ultrasonic dispersion, and add ammonia water to adjust the pH value to 10 to obtain solution B. Prepare a 200 g / L tetraethyl silicate anhydrous ethanol solution C, and then drop 25 ml of solution C into the continuously stirred solution B, and heat it in a constant temperature water bath at 60 ° C for 7 hours. The final product is separated by a centrifuge, repeatedly washed with deionized water and anhydrous ethanol, dried in a drying oven, and ground to obtain core-shell structured silica-coated polymethyl methacrylate nanocomposite microspheres.

[0052] (3) Preparation of PMMA / SiO2 / CeO2 composite abrasive:

[0053] 4g of PMMA / SiO2 composite microspheres were added to 250ml of deionized water for ultrasonic dispersion to obtain solution D; 5g of soluble cerium salt was added to solution D, and then 10g of hexamethylenetetramine was added to obtain solution E, which was heated in a constant temperature water bath at 85°C and reacted for 4h under continuous stirring. The final product was separated by a centrifuge, repeatedly washed with deionized water and anhydrous ethanol, dried in a drying oven, and ground to obtain a PMMA / SiO2 / CeO2 nanocomposite abrasive with a double-shell structure.

[0054] SEM detection shows that the particle size of the PMMA microspheres prepared by the method of the present invention is 250-300 nm, the particle size of the PMMA / SiO2 composite microspheres is 260-330 nm, and the particle size of the PMMA / SiO2 / CeO2 nanocomposite abrasive is 280-365 nm.

[0055] Comparative experiment 1

[0056] A method for preparing a nano PMMA core-coated CeO2 shell abrasive comprises the following steps:

[0057] (1) Preparation of polymethyl methacrylate microspheres:

[0058] 20 g of methyl methacrylate was measured and washed with 10% sodium hydroxide. The washed methyl methacrylate was added to 120 ml of deionized water, and then 2 g of 3-(methacryloyloxy)propyltrimethoxysilane was added to prepare a mixed solution A. The mixed solution A was ultrasonically dispersed and heated to boiling in a constant temperature oil bath. After 5 minutes, 20 ml of a 100 g / L aqueous solution of 2,2'-azobisisobutylamidine dihydrochloride was added under stirring. After reacting for 2 hours, the mixture was cooled to obtain a uniformly dispersed PMMA microsphere emulsion.

[0059] (2) Preparation of PMMA / CeO2 composite abrasive:

[0060] Take 20 ml of the PMMA microsphere emulsion prepared in step 1 and add it to 200 ml of deionized water for ultrasonic dispersion to obtain solution D; add 3 g of soluble cerium salt to solution D, and then add 6 g of hexamethylenetetramine to obtain solution E, which is heated in a constant temperature water bath at 75°C and reacted for 3 hours under continuous stirring. The final product is separated by a centrifuge, repeatedly washed with deionized water and anhydrous ethanol, dried in a drying oven, and ground to obtain a PMMA / CeO2 nanocomposite abrasive with a double-shell structure.

[0061] Comparative experiment 2

[0062] Based on Example 1, only the amount of 3-(methacryloyloxy)propyltrimethoxysilane (MPS) in step (1) was changed to study its effect on the abrasive of the present invention. Specifically, the amount of MPS was 0 g, 1 g, 1.5 g, 2 g, 3 g, and 4 g, respectively. The experiment obtained a series of PMMA microspheres with different particle sizes, as shown in Table 1 below.

[0063] Table 1. Statistical table of the effect of different amounts of 3-(methacryloyloxy)propyltrimethoxysilane (MPS) on the particle size of PMMA microspheres.

[0064] From the data in Table 1, it can be seen that after adding MPS, the PMMA particle size is significantly reduced. With the increase of MPS dosage, the particle size of PMMA microspheres continues to increase. When the dosage of MPS reaches 2g, the particle size of PMMA microspheres is basically stable at about 295nm.

[0065] like Figure 4 Shown are TEM images of PMMA / SiO2 composite microspheres prepared without adding MPS and with adding 2 g of MPS according to the present invention.

[0066] from Figure 4 As can be seen in (a), when MPS is not added, the surface of PMMA microspheres is not coated with SiO2. After adding MPS, SiO2 particles are coated on the surface of PMMA microspheres and grow into a strawberry shape (e.g. Figure 4 (b)). This is because there is a weak interaction between SiO2 and PMMA, and mechanical stirring can easily destroy the interaction between SiO2 and PMMA. After adding MPS, the lipophilic alkyl group at one end can react with the hydroxyl group on the surface of PMMA to achieve anchoring, significantly improve the dispersibility of PMMA microspheres, and promote the uniform coating of SiO2 on the surface of PMMA microspheres.

[0067] Comparative experiment 3

[0068] On the basis of Example 1, only the concentration of tetraethyl silicate ethanol solution in step (2) was changed to study its effect on the material of the present invention. Specifically, the concentrations of tetraethyl silicate ethanol solution were 40, 120, and 200 g / L, respectively; this experiment obtained a series of PMMA / SiO2 composite microspheres with different SiO2 layer thicknesses.

[0069] like Figure 5 The SEM images of PMMA / SiO2 composite microspheres prepared at three tetraethyl silicate dosages of the present invention are shown. It can be seen from the figure that when the tetraethyl silicate dosage is 40 g / L, the number of SiO2 particles generated is small and a complete coating layer ( Figure 5(a)). When the dosage of tetraethyl silicate was 120 g / L, the number of SiO2 particles generated increased significantly, and a complete SiO2 layer was formed on the surface of PMMA microspheres ( Figure 5 (b)). When the amount of tetraethyl silicate increased to 200 g / L, the SiO2 layer became thicker and a large number of secondary nucleated SiO2 particles were generated ( Figure 5 (c)).

[0070] Comparative experiment 4

[0071] Based on Example 1, only the amount of cerium nitrate in step (3) was changed to study its effect on the material of the present invention. Specifically, the amount of cerium nitrate was 1g and 6g respectively, and the experiment obtained different CeO2 layer thicknesses and formed PMMA / SiO2 / CeO2 composite abrasives.

[0072] like Figure 6 The TEM images of the PMMA / SiO2 / CeO2 composite abrasive prepared by using different amounts of cerium nitrate in the present invention are shown in FIG. Figure 6 It can be seen that when the dosage of cerium nitrate is 1g, Ce 3+ The number of nuclei is small and cannot completely cover the surface of PMMA / SiO2 composite microspheres ( Figure 6 (a)). When the amount of cerium nitrate is 6g, Ce 3+ The number of nuclei increased significantly, and they were electrostatically adsorbed on the surface of PMMA / SiO2 composite microspheres, eventually forming a complete CeO2 layer ( Figure 6 (as shown in (b)).

[0073] Comparative experiment 5

[0074] The polishing performance of the PMMA / SiO2 / CeO2 composite abrasive prepared in Example 1 and the PMMA / CeO2 composite abrasive prepared in Comparative Experiment 1 was compared and studied. The specific method is as follows:

[0075] The composite abrasives prepared in Examples 1 and 4 were prepared into 1w% polishing slurry with anhydrous ethanol and ultrasonically dispersed for 10 minutes.

[0076] (2) Apply a polishing pressure of 21.43 kPa, set the polishing disk speed to 150 r / min, and the polishing slurry flow rate to 100 ml / min, and polish the KDP crystal surface for 10 min each time.

[0077] (3) Use an atomic force microscope (AFM) to detect the surface flatness of the polished crystal. Record the mass loss of the crystal after polishing. Repeat polishing 4 times, calculate the average loss of crystal mass 4 times, and deduce the removal rate of KDP crystal material.

[0078] After polishing with the composite abrasive prepared in Example 1, the roughness Ra of the KDP crystal surface in the same range is 0.46 nm (e.g. Figure 7 (b)), the material removal rate is 187nm / min. After the composite abrasive polishing obtained in the comparative experiment 1, the roughness Ra of the KDP crystal surface within the range of 5μm×5μm is 0.55nm (such as Figure 7 (a)), the material removal rate is 148nm / min. Comparative analysis shows that the nano PMMA core-coated SiO2 / CeO2 double-shell abrasive prepared by the present invention can achieve higher polishing efficiency while ensuring the polishing surface finish.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a double-shell abrasive with nano PMMA as the core and SiO2 / CeO2 as the coating, characterized in that: The steps include: Step 1, preparing PMMA microspheres by soap-free emulsion polymerization: washing methyl methacrylate with sodium hydroxide solution, adding the washed methyl methacrylate to deionized water, and then adding 3-(methacryloyloxy)propyltrimethoxysilane to prepare a mixed solution A, ultrasonically dispersing the mixed solution A, and heating it to boiling in a constant temperature oil bath; adding 2,2'-azobisisobutylamidine dihydrochloride aqueous solution under stirring conditions to react, and cooling after the reaction is completed to obtain a uniformly dispersed PMMA microsphere emulsion; Step 2, preparing PMMA / SiO2 nanocomposite microspheres by sol-gel method: taking the PMMA microsphere emulsion prepared in step 1, adding it into anhydrous ethanol for ultrasonic dispersion, adding ammonia water to adjust the pH value to 8-10 to obtain solution B; preparing anhydrous ethanol solution C of tetraethyl silicate with a concentration of 40-200 g / L, and then dropping solution C into the continuously stirred solution B, and heating the reaction in a constant temperature water bath; centrifuging the final product, and repeatedly washing it with deionized water and anhydrous ethanol, and then drying it, and grinding it to obtain core-shell structured silica-coated polymethyl methacrylate nanocomposite microspheres; Step 3, prepare PMMA / SiO2 / CeO2 composite abrasive by uniform precipitation method: take the silica-coated polymethyl methacrylate nanocomposite microspheres prepared in step 2, add them into deionized water for ultrasonic dispersion to obtain solution D; add soluble cerium salt to solution D, and then add hexamethylenetetramine to obtain solution E, heat it in a constant temperature water bath, and react under continuous stirring; the final product is centrifuged and repeatedly washed with deionized water and anhydrous ethanol, and then dried, and ground to obtain PMMA / SiO2 / CeO2 nanocomposite abrasive with a double shell structure.

2. The method for preparing a double-shell abrasive with a nano PMMA core coated with SiO2 / CeO2 according to claim 1, characterized in that: In step 1, the concentration of the sodium hydroxide solution is 10%.

3. The method for preparing a double-shell abrasive with a nano PMMA core coated with SiO2 / CeO2 according to claim 1, characterized in that: In step 1, the dosage of methyl methacrylate and deionized water is 10-30 g: 100-150 ml; the dosage of 3-(methacryloyloxy)propyltrimethoxysilane and methyl methacrylate is 1-4 g: 10-30 g; 20 ml of 50-200 g / L 2,2'-azobisisobutylamidine dihydrochloride aqueous solution is added, react for 1.5-3 h, and then cool to obtain a uniformly dispersed PMMA microsphere emulsion.

4. The method for preparing a double-shell abrasive with a nano PMMA core coated with SiO2 / CeO2 according to claim 3, characterized in that: In step 2, 10-60 ml of the PMMA microsphere emulsion prepared in step 1 is added to 50-100 ml of anhydrous ethanol for ultrasonic dispersion; 25 ml of solution C is added dropwise to the continuously stirred solution B; the constant temperature water bath is heated to 30-60° C., and the reaction time is 4-7 hours.

5. The method for preparing a double-shell abrasive with a nano PMMA core coated with SiO2 / CeO2 according to claim 4, characterized in that: In step 3, 0.5-4 g of PMMA / SiO2 composite microspheres are added to 100-250 ml of deionized water for ultrasonic dispersion to obtain solution D; 1-5 g of soluble cerium salt is added to solution D, and then 2-10 g of hexamethylenetetramine is added to obtain solution E; a constant temperature water bath is used for heating at 60-85°C, and the reaction is carried out for 2-4 h under continuous stirring.

6. The method for preparing a double-shell abrasive with nano PMMA as the core coated with SiO2 / CeO2 according to claim 1, characterized in that: In step 3, the soluble cerium salt is any one of cerium nitrate, cerium sulfate and cerium chloride or a combination thereof.

Citation Information

Patent Citations

  • Functional composite microsphere with pomegranate-shaped structure and preparation method of functional composite microsphere

    CN104525067A

  • Hybrid abrasive as well as preparation method and uses thereof in ultra-precision polishing

    CN104531067A

  • Preparation method and application of gamma-Al2O3 / SiO2 / CeO2 nano composite abrasive particle with core-shell three-layer structure

    CN118516079A